2015
DOI: 10.1155/2015/246398
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Rescuers’ Gender and Body Mass Index on Cardiopulmonary Resuscitation according to the American Heart Association 2010 Resuscitation Guidelines

Abstract: Background and Objectives. The quality of cardiopulmonary resuscitation (CPR) is an important factor in determining its overall outcome. This study aims to test the association between rescuers' gender, Body Mass Index (BMI), and the accuracy of chest compressions (CC) as well as ventilation, according to American Heart Association (AHA) 2010 resuscitation guidelines. Methods. The study included 72 participants of both genders. All the participants received CPR training according to AHA 2010 resuscitation guid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 15 publications
2
5
0
1
Order By: Relevance
“…Results from this analysis showed that younger heavier rescuers were more likely to achieve a greater depth. This is consistent with the findings of other studies that suggest a positive relationship between rescuer weight and adequacy of compressions 16,20,21,26 . It is also possible that younger participants have a higher proportion of lean muscle, more cardiovascular fitness or a less nihilistic approach; this is purely speculative, however is consistent with work recently published by Tellson et al 16,21 .…”
Section: Discussionsupporting
confidence: 92%
“…Results from this analysis showed that younger heavier rescuers were more likely to achieve a greater depth. This is consistent with the findings of other studies that suggest a positive relationship between rescuer weight and adequacy of compressions 16,20,21,26 . It is also possible that younger participants have a higher proportion of lean muscle, more cardiovascular fitness or a less nihilistic approach; this is purely speculative, however is consistent with work recently published by Tellson et al 16,21 .…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, men performed more chest compressions with the correct rate on the baby manikin, which contradicts previous evidence. In resuscitation studies on adult manikins, researchers observed that women performed CPR with higher compression rates than men . In our study, the males achieved better complete chest recoil with the baby manikin than females.…”
Section: Discussionsupporting
confidence: 52%
“…Cardiopulmonary resuscitation quality can be affected by many different factors, such as whether the rescuer feels stress or fatigue, their medical experience and the medical equipment available at the scene. Studies have reported that anthropometric variables, such as body height and weight, may influence chest compression quality to a certain extent . However, the results of these studies were limited by the small number of participants and they tended to focus on basic life support for adults.…”
Section: Introductionmentioning
confidence: 99%
“…There are studies that associate chest compressions with sex. Although some studies show no difference [911], most studies have shown a decrease in chest compression depth when CPR is performed by female participants [1225]. Under certain conditions, sex differences become more marked.…”
Section: Discussionmentioning
confidence: 99%